Woody debris production and deposition during floods at extreme rainfall period 2012-2013 in Yabe and Tsuwano River Basin, Japan - Muhammad Islamy Rusyda; Sinya Ikematsu; Haruyuki Hashimoto (Indonesian Journal of Geography, 2020)
The behavior of woody debris has become a critical issue in river dynamics. It is still not widely understood, particularly during a flood event. Field investigations were performed to investigate the characteristics of woody debris production and deposition during the 2012 and 2013 floods in Yabe and Tsuwano River Basin, Japan. Ground-level photos, aerial photos, and direct measurements were used to measure the length and diameter of woody debris,   characteristics of obstacles (length. width, diameter, and shape). These investigations revealed that woody debris deposition was divided into two types: the rest of individual woody debris pieces on the riverside slope or floodplain and the formation of a woody debris jam at obstacles such as bridges, riparian trees, houses, and irregular topographic relief. Individual woody debris pieces at the production sites are around two times longer than those at the deposition sites. However, the variation coefficient of piece length at the production sites is smaller than that at the deposition site. Our results also show that the most extended piece in the jam and horizontal scale of the obstacle are two essential factors in jam formation. An empirical equation for predicting the apparent volume of jam at an obstacle is also proposed.